2018
DOI: 10.1177/1474515118777391
|View full text |Cite
|
Sign up to set email alerts
|

The second myocardial infarction: Is there any difference in symptoms and prehospital delay compared to the first myocardial infarction?

Abstract: Symptoms of second myocardial infarctions are not necessarily the same as those of first myocardial infarctions. A patient's behaviour at the first myocardial infarction could predict how he or she would behave at a second myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
2
8
0
1
Order By: Relevance
“…This is in line with previous results from studies based on questionnaires and medical records. 20,[30][31][32] For most patients in our study, there was good consistency between symptoms reported in calls and symptoms reported in questionnaires, with 2 exceptions: fear and tiredness. These symptoms were more often reported in questionnaires than described in the calls.…”
Section: Discussionsupporting
confidence: 63%
“…This is in line with previous results from studies based on questionnaires and medical records. 20,[30][31][32] For most patients in our study, there was good consistency between symptoms reported in calls and symptoms reported in questionnaires, with 2 exceptions: fear and tiredness. These symptoms were more often reported in questionnaires than described in the calls.…”
Section: Discussionsupporting
confidence: 63%
“…Strömbäck et al showed that the appearance of atypical symptoms in a second AMI was not a predictor of a longer delay time [116]. One reason for this observation might be that a history of AMI seems to increase symptom congruence [111].…”
Section: Knowledge and Its Relationship To Cardiac Attributionmentioning
confidence: 99%
“…Интересными, на наш взгляд, были результаты шведского исследования (820 больных), в котором изучались характер симптомов острого ИМ и динамика временного интервала от начала симптомов заболевания до ПМК при первичном и повторном ИМ у одного и того же пациента [46]. Примечательным было то, что небольшое количество пациентов (10% мужчин и 16,2% женщин) сообщали о различном характере симптомов при первичном и повторном ИМ.…”
Section: вмешательства направленные на повышение грамотности населенunclassified